Development of an Industrial-Scale Coffee Drying Technology: Energy Efficiency and Sustainability Assessment - Richard A. Williams; Maria V. Sanchez-Delgado; John M. Dennis; Eleanor C. Sharpe; Samuel J. Pettinger (Gio Vani Publisher, 2026)
This study addresses the critical need for energy-efficient and sustainable technologies in industrial coffee processing by developing and evaluating a novel waste-heat recovery preheater integrated into a coffee roasting system. The research experimentally investigates the impact of preheating on the thermal dynamics, energy efficiency, and product quality of Robusta coffee beans at a laboratory scale. Results demonstrate that utilizing exhaust heat to pre-condition beans significantly enhances process performance, achieving a 62.33% reduction in overall energy consumption and a 60.65% decrease in LPG fuel use. The preheating mechanism accelerated the roasting kinetics, reducing the time to target roast level by 2–3 minutes and improving moisture removal efficiency, yielding a final bean moisture content of 1.6% compared to 3.1% in the conventional process. These findings validate the preheater as a highly effective intervention for optimizing heat and mass transfer. The study concludes that integrating such waste-heat recovery technology presents a viable, scalable pathway for decarbonizing industrial-scale coffee drying and roasting operations, directly contributing to enhanced energy efficiency, reduced carbon footprint, and improved economic viability within the global coffee supply chain.